ANALISIS EFEKTIVITAS PENERAPAN MANAJEMEN BERBASIS SEKOLAH - Chindytia; Anak Agung Gede Agung; Ni Made Ayu Estya Apsari; Ni Kadek Fanya Pertiwi Putri; Ni Luh Putu Amara Dharmayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of School-Based Management (SBM) in improving the quality of education in schools. The research method used is a literature study by collecting and analyzing various scientific sources, such as journals, books, theses, dissertations, and other supporting documents relevant to the research topic. The literature used was published between 2021–2026 and obtained through online and offline library searches. The results of the study indicate that SBM is an educational management strategy that provides schools with autonomy in managing resources independently, participatively, transparently, and accountably. The implementation of SBM is carried out through the stages of understanding, implementation, and strengthening, which aim to improve the effectiveness of school management. The application of SBM has been proven to improve the quality of learning, teacher performance, community participation, and student learning outcomes. The success of SBM implementation is influenced by several supporting factors, such as visionary school leadership, adequate resources, effective communication, community participation, and the use of technology. However, the implementation of SBM also faces several obstacles, including limited facilities and infrastructure, low human resource competence, limited funding, and lack of optimal community support. Therefore, cooperation among all school members, improvement of teacher competence, and support from the government and the community are needed so that the implementation of SBM can run optimally and sustainably in improving the quality of education.